An AN ANALYSIS OF THE IMPACT OF NOVEL CORONAVIRUS PANDEMIC (COVID-19) ON STATE-OWNED ENTERPRISES IN ZIMBABWE. A CASE STUDY OF THE NATIONAL SOCIAL SECURITY AUTHORITY (NSSA) - Mbambi, Titos; Maximilian, Dr Chiunye Tonderai (International Journal For Research In Business, Management And Accounting, 2022)
The study sought to unearth the impact coronavirus pandemic (Covid-19) on State-Owned Enterprises (SOEs) in Zimbabwe. The study was prompted by lock-downs, curfews and limiting of numbers of workers allowed to be at work places around the country as directed by Government in compliance with the World Health Organisation (WHO) Protocols. This was mean to save human lives as the pandemic ravaged the whole world unsparingly. The closure of businesses as measures to combat the spread and ultimate loss of human lives crippled businesses small and big alike. SOEs were not spared either as the pandemic spread like veld-fire as world health leaders engaged each other for possible solutions. This study employed a case study because of its appropriateness in the exploration of the SOE in its true business setting. It also allowed the researcher to uncover the impact of Covid-19 and the remedial actions to ensure its survival in the face of implementation of protocols to contain the pandemic. The target population were 40 operational managers of the SOE with real knowledge of the operations of the SOE’s different departments. A sample of 20 respondents was used to obtain data responses. Purposive sampling was most ideal in this study as the target was known and comprised of operational managers with information on business of the SOE. The major findings were that the SOE was not spared by the pandemic but diligently implemented health protocols to abate severe consequences as well as promoting the ease of doing business. The major recommendations were that parastatals needed to invest in technology to ensure that people can work from anywhere without necessarily being at the office as well as employing a hybrid type of work environment to manage future disasters should they strike.